STUDI KOMPARASI KITAB ADAB AL-‘ALIM WA AL-MUTA’ALLIM KARYA KH. HASYIM ASY'ARI DAN KITAB HILYAH THALIB AL-'ILMI KARYA SYAIKH BAKR BIN ABDULLAH ABU ZAID TENTANG ETIKA PENUNTUT ILMU - Husni, Karna (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2023)
The study is inspired by the importance of the role of ethics as the initial point of foundation in education, because education in principle is to bring and foster a person's mental better. This study aims to determine the concept of ethics or manners and morals of a student according to KH. Hasyim Asy'ari in the Book of Adabul 'Alim Wal Muta'allim and Sheikh Bakr in the Book of Hilyah Tholib Al-'Ilmi and the similarities and differences in the concept of students from the two books. This research uses a qualitative approach with an analytical descriptive method through the Library Research method, namely research activities that are sourced from literature books. The results of this study are: 1) The concept of adab and morals of knowledge seekers in the book Adabul 'Alim Wal Muta'allim consists of four aspects of adab and morals that must be carried out by knowledge seekers, namely: a) Manners for Seekers of Knowledge (Students), b) Manners of Students Toward Teachers, c) Manners of Learning for Seekers of Knowledge, d) Manners Toward Books. 2) The concept of manners and morals of knowledge seekers in the book Hilyah Talib Al-'Ilmi consists of four aspects of manners and morals that must adorn a knowledge seeker, namely: a) Manners for the person of a knowledge seeker, b) Manners for a knowledge seeker to his teacher, c) Manners for a knowledge seeker to his friend and d) Manners for a knowledge seeker in an atmosphere of seeking knowledge. 3) The similarities between the concepts of adab and morals of knowledge seekers in the two books are: a) The concept of student manners and morals explained by KH. Hasyim Asy'ari and Sheikh Bakr both equally emphasize the aspect of empowering the heart, b) The thoughts of the two figures both discuss the urgency and understanding of ethics or manners and morals as a student into chapters that are written and become important points. c) In the contents of the two books, they both discuss the same two chapters, namely the chapter on morals and manners as a student for his person and the morals of students to their teachers, while the other chapters are very different.